Pseudomonas pyocyanea and the arginine dihydrolase system - Taylor, J. J. (1964)
Non-pigmented strains of Pseudomonas pyocyanea occur frequently and this organism has only limited activity in conventional biochemical tests; 50 strains were tested for the presence of arginine dihydrolase and found positive whereas only Salmonella sp. and Enterobacter sp. among other Gram-negative species were positive. The test for arginine dihydrolase is rapid and simple and suitable for routine use.